Revolutionizing Surgery: The Impact of Machine Learning and Artificial Intelligence on Surgical Robotics - Yuan, Weihang (Transactions on Computer Science and Intelligent Systems Research, 2024)
This article examines the transformative impact of machine learning (ML) and artificial intelligence (AI) on surgical robotics, highlighting the advancements that have significantly enhanced precision, efficiency, and safety in surgeries. The integration of these technologies has enabled surgical robots to perform complex tasks autonomously, with accuracy rates approaching those of human surgeons. Key developments include improved surgical tool tracking, real-time data analysis, and enhanced decision-making capabilities during operations, which collectively contribute to reducing operation times and complication rates. The discussion extends to the potential future directions of these technologies, emphasizing continuous improvement in human-robot interaction, regulatory adaptations, and broader application across various medical fields. The anticipated advancements are expected to make high-quality surgical interventions more accessible, particularly in remote and underserved areas, ultimately revolutionizing patient care by making surgeries safer, faster, and more patient-centered. The article underscores the role of ongoing research and development in pushing the boundaries of what surgical robots can achieve, setting the stage for a new era in medical technology.